Overview of Oncology: Drug-Induced Cardiac Toxicity - Nilima Rajpal Kundnani; Vincenzo Passini; Iulia Stefania Carlogea; Patrick Dumitrescu; Vlad Meche; Roxana Buzas; Daniel Marius Duda-Seiman (Medicina)
Cancer medications can cause cardiac issues, which are difficult to treat in oncologic patients because of the risk of complications. In some cases, this may significantly impact their well-being and treatment outcomes. Overall, these complications fall under the term “drug induced cardiotoxicity”, mainly due to chemotherapy drugs being specifically toxic to the heart, causing a decrease in the heart’s capacity to pump blood efficiently and leading to a reduction in the left ventricular ejection fraction (LVEF), and subsequently possibly leading to heart failure. Anthracyclines, alkylating agents, and targeted therapies for cancer hold the potential of causing harmful effects on the heart. The incidence of heart-related issues varies from patient to patient and depends on multiple factors, including the type of medication, dosage, duration of the treatment, and pre-existing heart conditions. The underlying mechanism leading to oncologic-drug-induced cardiovascular harmful effects is quite complex. One particular group of drugs, called anthracyclines, have garnered attention due to their impact on oxidative stress and their ability to cause direct harm to heart muscle cells. Reactive oxygen species (ROS) cause harm by inducing damage and programmed cell death in heart cells. Conventional biomarkers alone can only indicate some degree of damage that has already occurred and, therefore, early detection is key. Novel methods like genetic profiling are being developed to detect individuals at risk, prior to the onset of clinical symptoms. Key management strategies—including early detection, personalized medicine approaches, and the use of novel biomarkers—play a crucial role in mitigating cardiotoxicity and improving patient outcomes. Identification of generated genetic alterations and the association to an increased likelihood of cardiotoxicity will allow treatment in a more personalized approach, aiming at decreasing rates of cardiac events while maintaining high oncological efficacy. Oncology drug-induced cardiotoxicity is managed through a combination of preventive strategies and therapeutic interventions from the union of cardiac and oncological knowledge.